Assessment of Density and Anatomical Features of Young and Old Bambusa vulgaris (Schrad. ex J.C. Wendl.) Culm Heights as Sustainable Structural Material in Ghana - Michael Awotwe-Mensah; Emmanuel Appiah-Kubi; Stephen Jobson Mitchual (International Journal of Forestry Research)
This study sought to assess the density and anatomical features of young and old Bambusa vulgaris Schrad. ex JC Wendl. culm heights and, therefore, evaluate their influence on the utilization potential of the culm as a sustainable structural material. Bambusa vulgaris culm of 2-year and 4-year-old were harvested and prepared to the required length of 6 meters for the study. Basic density and anatomical features were carried out. The results showed that the basic density of old bamboo ranges from 652.91 kg/m³ to 729.06 kg/m³, while the young bamboo ranges from 342.33 kg/m³ to 509.52 kg/m³. The vascular bundle arrangement was found to be in Type III and Type IV for the culm heights of both young and old bamboo. The average vascular bundle radial diameter ranged from 761.13 μm to 890.78 μm for the old culm and 727.16 μm to 844.83 μm for the young culm. The average vascular bundle tangential diameter ranged from 499.44 μm to 533.49 μm for the old culm and 425.56 μm to 483.56 μm for the young culm. The radial diameter of the metaxylem vessel of the old culm ranged from 216.81 μm to 54.74 μm, while 214.23 μm to 73.86 μm were for the young culm. Parenchyma tissues ranged from 35%– to 70% for the old bamboo culm and 45% to 75% for the young bamboo culm. Vessel proportion ranged from 6%–12% for the old culm while the young culm ranged from 5%–11%. Fiber proportion ranged from 22% to 54% for the old culm and 19% to 44% for the young culm. Old bamboo had better vascular bundle properties than that of young bamboo. The density is significantly correlated positively to the anatomical properties. Old bamboo is more suitable to be used as the engineered composite material due to its better anatomical features across the culm wall thickness.